Assessment of Effective Oral Health Status among Diabetic population by Modified Special Tooth Brush with Beat SoundAn observational study - Vijay Anand. M1 , Keerthi Narayan. V2 , Kalaivani. S3 , Safa Thabassum. S3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background of the study: Proper guided brushing technique improves the oral health status especially among diabetic individuals who are more susceptible for periodontal disease. Aim and objective: To find the outcome efficacy of modified design special tooth brush with beat sound by evaluating oral hygiene status among diabetic individuals.Material and methods:The present observational study included 25 study participants irrespective of age and gender divided and categorized as 13 non-diabetic (control) group and 12 belong to diabetic (study) group. All the study participants were educated to use modified special tooth brush with beat sound regularly for a period of 1 week and their oral hygiene status were evaluated by using Oral hygiene index simplified (OHI-S), periodontal index (PI) and Gingival index (GI) at regular intervals on 1st, 3rd, 5th and 7th day. Results: It was observed that all the study participants showed significant improvement in oral health status at the end of 7th day. It was also observed that diabetic individuals showed superior OHI-S (P=0.002), PI (P=0.0001) and GI (P=0.0004) scores with greater significance (p<.05) than non-diabetic individuals. Conclusion: From the above results it can be concluded that the modified special tooth brush with beat sound used in the present study can reduce the burden of periodontal disease status by improving oral health among diabetic individuals.